Translation and Cross-Cultural Adaptation of Nepali Version of the Montreal Cognitive Assessment - Gyawali, Manju; Tretriluxana, Jarugool; Chaiyawat, Pakaratee; Jalayondeja, Chutima; Shrestha, Bishwas (Journal of Nepal Health Research Council, 2023)
Background: Montreal Cognitive Assessment is widely used in stroke to detect cognitive impairment. The superiority of it over other outcome measures has been well established. It has been cross-culturally translated and has shown excellent psychometric properties. To assess the intervention effect on cognition of Nepalese individuals with stroke using the Montreal Cognitive Assessment, an adapted Nepali version is required as the Nepalese cultural context and language are completely different than the original was developed. Thus, the objective of this study is to translate and cross-culturally adapt Montreal Cognitive Assessment in the Nepali language and see its test-retest reliability and internal consistency. Methods: After translating and cross-culturally adapting the Montreal Cognitive Assessment into Nepali using Beaton guidelines. Its Nepali version was administered to 28 individuals with stroke twice keeping the interval of two weeks. Test-retest reliability and internal consistency were assessed using the Intraclass correlation coefficient and Cronbach’s alpha. Results: The Montreal Cognitive Assessment was translated into Nepali with significant cultural adaptations and the Nepali version demonstrated excellent psychometric properties as hypothesized. The test-retest reliability and internal Consistency were excellent. The Intraclass correlation coefficient of the total score was 0.990 and Cronbach’s alpha value was 0.994 for total scores. Conclusions: The Nepali version of Montreal Cognitive Assessment is reliable to use as a diagnostic tool for detecting cognitive impairment in patients with stroke. It is comprehensive, easy to administer and culturally appropriate. Keywords: Cognition; montreal cognitive assessment (MoCA); outcome measure; reliability; stroke